Postmodernism Creates Innovative English Teaching Learning by Utilizing ICT - Yustin Dwi Rahmawati (English Learning Innovation (englie), 2021)
Through comprehensive literature review and an examination of both Postmodernism and ICT, it is proposed that the influences of ICT have acted and continued to act to promote Postmodernism. The development of ICT is utilized by education field for teaching learning process. Many teachers and students utilize the existing of ICT as model of teaching and learning especially English. This study discussed about teachers’ belief and students’ belief in using ICT to have innovative English teaching learning. Qualitative descriptive was used in this study. The data was collected by conducting the interview. The participants were five English teachers and five students that chose randomly. The result showed that both teachers’ and students’ belief in using ICT is to make English teaching learning easier, more interesting, and effective. Keywords:Postmodernism,ICT, teachers’ belief, students’ belief